Bisphenol analogues induced metabolic effects through eliciting intestinal cell heterogeneous response. (July 2022) - Mu, Xiyan; Qi, Suzhen; Wang, Hui; Yuan, Lilai; Wang, Chengju; Li, Yingren; Qiu, Jing
Graphical abstract: Abstract: The metabolic effects of endocrine-disrupting chemicals, such as bisphenol analogues, have drawn increasing attention. Bisphenol A (BPA) usage is associated with the occurrence of many metabolic diseases. With the restricted use of BPA, alternatives like bisphenol F (BPF) and bisphenol AF (BPAF) have been greatly introduced for industrial manufacture, and brings new hazard to public health. To understand how bisphenol analogues induced metabolic effects, zebrafish are continuous exposed to environmental level (0.5 μg/L) of BPA, BPF and BPAF since embryonic stage, and identified hepatic steatosis and insulin resistance at 60-day post fertilization. Hepatic transcriptional profile indicated that pancreatic disease pathways were activated by BPA, but were inhibited by BPF. At the same time, increased lipid secretion and gluconeogenesis pathways in zebrafish liver was found post BPAF exposure. Significant inflammatory response, histological injury and increased mucus secretion was detected in zebrafish intestine post exposure of three bisphenol analogues. Single-cell RNA sequencing of zebrafish intestinal cells revealed activation of lipid uptake and absorption pathways in enterocyte lineages, which well explained the hepatic steatosis induced by BPA and BPF. Besides, genes related to carbohydrate metabolism, diabetes and insulin resistance were activated in intestinal immune cell types by three bisphenol analogues. These findings indicated that BPA and its alternatives could lead to abnormal lipid and carbohydrate metabolism of zebrafish through inducing cell heterogeneous changes in gut, and revealed both molecular and cellular mechanism in mediating this effect.